Climate Change and its Effects on Right to Health and other Related Human Rights - Ehsan Azizi; Alireza Arashpour; Leila Raisi Dezaki (Shiraz University of Medical Sciences, 2017)
During the last two centuries, human being has emitted huge amounts of greenhouse gases to the atmosphere, by providing energy from fossil fuels. The increasing accumulation of these gases in the atmosphere has led to "global warming" and as a result "climate change". This inauspicious phenomenon has such a wide domain that threat the survival of the human around the world. The sharp decline in fresh water sources and strategic agricultural products and severe destruction of environment are just some inevitable adverse effects of climate change. Therefore, it would be a proper ground for breaching some of the most important human rights. The aim of this research is to show effects of climate change on "right to health" and some other related rights, and therefore responsibilities of governments to fight against that.  Conclusion: Climate change due to human activities, makes a proper field for breach of human rights globally, and as we see "right to health" is affected absolutely. According to principal of "common but differentiated responsibilities", most of the burdens of combating against climate change are on the shoulders of developed states and developing countries have much less obligations; but at least have common responsibilities. Rather, all of the states have clear international obligations for protecting human rights in their territories. Therefore any state must separately or together with others, take urgent and also long term measures to fight this phenomenon. If climate change continues; negligence of states in performing due diligence in this regard may lead to their international responsibility or even their incapability for governing the state in accordance with "good governance principles".